Ropinirole alters gene expression profiles in SH-SY5Y cells: a whole genome microarray study - M.Z. Zhu; W.D. Le; G. Jin (Brazilian Journal of Medical and Biological Research, 2016)
Ropinirole (ROP) is a dopamine agonist that has been used as therapy for Parkinson's disease. In the present study, we aimed to detect whether gene expression was modulated by ROP in SH-SY5Y cells. SH-SY5Y cell lines were treated with 10 µM ROP for 2 h, after which total RNA was extracted for whole genome analysis. Gene expression profiling revealed that 113 genes were differentially expressed after ROP treatment compared with control cells. Further pathway analysis revealed modulation of the phosphatidylinositol 3-kinase (PI3K) signaling pathway, with prominent upregulation of PIK3C2B. Moreover, batches of regulated genes, including PIK3C2B, were found to be located on chromosome 1. These findings were validated by quantitative RT-PCR and Western blot analysis. Our study, therefore, revealed that ROP altered gene expression in SH-SY5Y cells, and future investigation of PIK3C2B and other loci on chromosome 1 may provide long-term implications for identifying novel target genes of Parkinson's disease.